2018
DOI: 10.21037/tlcr.2018.03.27
|View full text |Cite
|
Sign up to set email alerts
|

Decision analytic modeling for the economic analysis of proton radiotherapy for non-small cell lung cancer

Abstract: The comparison between proton and photon/X-ray radiation therapy for NSCLC needs to consider both the up-front cost of treatment and the possible long term cost of complications. In our analysis, current costs favor X-ray therapy. However, relatively small reductions in the cost of proton therapy may result in a shift to the preference for proton therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…There are some potential drawbacks in utilizing PBSPT. First, overall costs of PBT easily exceed those of photon RT, even after toxicity rate-adjusted analysis [ 37 ]. However, PBT increased the quality-adjusted life-years by 0.549 and 0.452 compared to 3D CRT/IMRT [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are some potential drawbacks in utilizing PBSPT. First, overall costs of PBT easily exceed those of photon RT, even after toxicity rate-adjusted analysis [ 37 ]. However, PBT increased the quality-adjusted life-years by 0.549 and 0.452 compared to 3D CRT/IMRT [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Grutters et al [74] recommended not adopting proton as a standard treatment for NSCLC. Though current costs favor photon therapy in most studies, the preference for proton therapy may be found with relatively small reductions in the cost of proton therapy [72]. Therefore, it is hard to draw a conclusion now, based on the present limited evidence of cost-effectiveness for proton therapy over other therapies in treating lung cancer.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Compared with photon therapy, the initial cost was 2.4-fold higher for proton therapy, however, after adding the costs of treating adverse effects, the total cost was reduced by 2.6-fold for proton therapy [70,71]. In a recent report using an influence diagram to model for radiation delivery in lung cancer, the overall costs (radiation plus toxicity costs) and upfront proton treatment costs exceeded that of photons [72]. The relatively lower rate of pneumonitis and esophagitis rates help protons to recover some of the total cost.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…18,20,21 Based on other literature found in the scoping review, PT was recommended for patients with early-stage or locally advanced NSCLC patients at high risk of developing severe acute side effects (e.g. elderly), 10,31,40 patients with tumours located centrally and close to the brachial plexus, and patients whose tumours or nodal involvement overlapped with or was inferior to T7. 46 Verma et al 13 and Smith et al 63 alternatively found PT was not effective for early-stage lung cancer or low-risk groups where cost differences between conventional and PT were minimal.…”
Section: Lung Tumoursmentioning
confidence: 99%